Pengaruh Model Pembelajaran Write Around Berbantuan Media Gambar Seri terhadap Kemampuan Menulis Cerita Dongeng - Solihin, Agisni Maulina; Nurmahanani, Indah; Iskandar, Sofyan (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The background of this research is the low skill of writing fairy tales by students which is indicated by the difficulty of students in finding and pouring ideas into written form. This study aims to determine: 1) students' fairy tales writing skill before applying the write around learning model assisted by picture series media; 2) students' fairy tales writing skill after applying the write around learning model assisted by picture series media; 3) the effect of the write around learning model assisted by picture series media on students' fairy tales writing skill. The type of research used is pre-experimental research type one group pretest-posttest. The sample of this research was class 4 in one of the elementary schools in Bandung, totaling 13 students. Based on the results of the study, the following conclusions were obtained: 1) the average value of the pretest results for students' fairy tales writing skill before applying the write around learning model assisted by picture series media was in the sufficient category; 2) the average value of the posttest results of students' fairy tales writing skill after applying the write around learning model assisted by picture series media is in the good category; 3) there is an effect of the write around learning model assisted by picture series media on students' fairy tales writing skill.